STUDYING THE METHOD OF COTTON AGAINST INSECTS IN THE MOLECULAR GENETIC CONTEXT (Proceedings of International Educators Conference, 2023)
The biggest threat to cotton in Uzbekistan is chatnik introduced winter cutworm (Agrotis segetum Den. and others Schiff), cotton spoon (Helicoverpa armigera Hbn.), spider mites (Tetranychus urticae Koch.), various types of aphids (Aphididae), insects are myridy (Miridae). This In the absence of effective control of pests, they destroy the cotton crop is losing, it can exceed 1.1 million tons per year due to the damage caused by these pests. This Special attention should be paid to pests, this type of insect is generative damages the organs. The period of their formation is the drying and immaturity of cotton brings.. In such growth, the exchange of body tissues is disturbed. From this besides, the nectar released from the cotton flower attracts aphids and insects. Sticky secretions winged flies cause mass development of the cellulose complex destroys microorganisms.